Isolation and characterization of carbazole and dibenzofuran degrading bacteria from soil in mangrove enviroment - Fatin Nur Sufinas, Bt Shuib (Faculty of Resource Science and Technology, 2013)
Heterocyclic hydrocarbons are toxic and mutagenic components of petroleum and creosote contamination that are frequently found in the groundwater, seawater, sediments, and soil sites. A study was carried out to isolate and characterize heterocyclic hydrocarbon degrading bacteria from soil samples collected at mangrove environment at Asajaya, Sarawak. This environment has physicochemical characteristics of high salinity, tidal range, strong winds, high temperature, crude oil and muddy soil. Crude oil often contains various heterocyclic compounds that are toxic for most life forms. Despite its toxicity, some bacteria species have the capability to mineralize these heterocyclic hydrocarbons compound efficiently. Two bacteria strains FNS01 and FNS02 was isolated and grown with enrichment of carbazole (CAR) and dibenzofuran (DBF) as the sole source of carbon. Characterization of these two isolated bacteria include motility test with the use of semi-solid medium, catalase test, salt tolerance test, hydrogen sulfide test, oxidase test, gram staining, and also different polycyclic aromatic hydrocarbons (PAHs) substrate test such as carbazole (CAR), biphenyl (BPH), fluorene (FLO), dibenzofuran (DBF), and dibenzothiophene (DBT) were studied. Total DNA was extracted and 16S rRNA amplified by PCR method and subsequently differentiates the species with restriction fragment length polymorphism (RFLP). Isolation of these strains might be useful in the bioremediation of environments contaminated by heterocyclic hydrocarbon.